Contrasting E−H Bond Activation Pathways of a Phosphanyl‐Phosphagallene. Issue 40 (31st August 2021) - Feld, Joey; Wilson, Daniel W. N.; Goicoechea, Jose M.
Abstract: The reactivity of the phosphanyl‐phosphagallene, [H2 C{N(Dipp)}]2 PP=Ga(Nacnac) (Nacnac=HC[C(Me)N(Dipp)]2 ; Dipp=2, 6‐ i Pr2 C6 H3 ) towards a series of reagents possessing E−H bonds (primary amines, ammonia, water, phenylacetylene, phenylphosphine, and phenylsilane) is reported. Two contrasting reaction pathways are observed, determined by the polarity of the E−H bonds of the substrates. In the case of protic reagents ( δ− E−H δ+ ), a frustrated Lewis pair type of mechanism is operational at room temperature, in which the gallium metal centre acts as a Lewis acid and the pendant phosphanyl moiety deprotonates the substrates. Interestingly, at elevated temperatures both NH2 i Pr and ammonia can react via a second, higher energy, pathway resulting in the hydroamination of the Ga=P bond. By contrast, with hydridic reagents ( δ+ E−H δ− ), such as phenylsilane, hydroelementation of the Ga=P bond is exclusively observed, in line with the polarisation of the Si−H and Ga=P bonds. Abstract : We describe the synthesis and reactivity of a phosphanyl phosphagallene towards reagents with protic and hydridic E−H bonds. These studies reveal that there are two competing reactivity pathways available for such bond activation reactions: a frustrated Lewis pair type of mechanism, and a competing pathway which results in the hydroelementation of the Ga=P double bond.